Relational and functional aspects of safety for patients and caregivers in intensive care: scoping review - Maria Aparecida Pereira dos Santos Santana; Eliana Rosa da Fonseca; Keroulay Estebanez Roque; Tony de Oliveira Figueiredo; Valentina Maria Dias de Souza; Marluci Andrade Conceição Stipp; Liana Amorim Correa Trotte (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To analyze the relational and functional aspects of patient safety through the experiences reported by the patients themselves and/or their caregivers in intensive care units. Method: Scoping review developed with searches, in September 2021 and updated in November 2022, in the following databases: Virtual Health Library, considering only the LILACS, BDENF, IBECS, ColecionaSUS databases; SCIELO, PsycINFO, EMBASE, COCHRANE, CINAHL, SCOPUS and Web of Science. Results: The final selection included 14 articles highlighting communication as an essential relational factor for care safety. The most predominant functional aspects were physical care environment, structured protocols, and the performance of professionals in the care process. Conclusion: Communication processes were predominant in relational aspects and were decisive for functional aspects, with emphasis on the performance of professionals in the care process. Instruments developed for quality process analysis were used in most of the studies.